(untitled) (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
Using the case of the province of Buenos Aires in the second half of the nineteenth century as a point of departure, this paper analyzes a problem often ignored by studies of the representative system and, in particular, political parties: the process through which political parties, in addition to being considered a legitimate and necessary institution for representative government, became the main or exclusive channel of political representation. Despite its importance, the process through which political parties emerged as a central feature of the political system has often been ignored. By studying this process, this article seeks to contribute to current debates on political representation and participation.